THE RISK OF SMARTPHONE ADDICTION TO EMOTIONAL MENTAL DISORDERS AMONG JUNIOR HIGH SCHOOL STUDENTS - Rizky Setiadi; Tini Tini; Edi Sukamto; Umi Kalsum (Belitung Nursing Journal, 2019)
Background: The use of smartphones increases in Indonesia, its users are no longer among adults but have also spread to teenagers and children. Smartphone addiction causes a variety of problems, both physical, social, behavioral, and psychological problems of adolescents. Objective: The objective of this study is to identify the association between the tendency of smartphone addiction and the occurrence of emotional mental disorders in adolescents of junior high school students in Samarinda. Methods: This study used a descriptive analytic design through cross-sectional approach conducted in junior high schools in Samarinda. Sample of this study were 127 students. The 20 self-questionnaire adopted from the 2013 Basic Health Research questionnaire was used to measure emotional mental disorders, and the Smartphone Addiction Scale - Short Version (SAS-SV) questionnaire was used to measure smartphone addiction. Data were analyzed with multiple logistic regressions. Results: Results showed that there was an association between smartphone addiction and emotional mental disorders among junior high school students in Samarinda (p < .05). Adjusted Odds Ratio (AOR) was obtained at 2.418 (95% CI was 1.033 – 5.660). Conclusions: Smartphone addiction may lead emotional mental disorder among Junior High School students. The decisive rules are needed in the use of smartphones, both at school and at home to prevent the occurrence of smartphone addiction.